Antiarrhythmic drug therapy after catheter ablation for atrial fibrillation—Insights from the German Ablation Registry. Issue 6 (19th October 2021) - Schleberger, Ruben; Metzner, Andreas; Kuck, Karl‐Heinz; Andresen, Dietrich; Willems, Stephan; Hoffmann, Ellen; Deneke, Thomas; Eckardt, Lars; Brachmann, Johannes; Hochadel, Matthias; Senges, Jochen; Rillig, Andreas
Abstract: Data on the optimal treatment strategy for antiarrhythmic drug therapy (AAD) after catheter ablation for atrial fibrillation (AF) are inconsistent. The present study investigates whether postinterventional AAD leads to an improved long‐term outcome. Patients from the prospective German Ablation Registry ( n  = 3275) discharged with or without AAD after catheter ablation for AF were compared regarding the rates of recurrences, reablations and cardiovascular events as well as patient reported outcomes during 12 months follow‐up. In patients with paroxysmal AF ( n  = 2138) the recurrence rate did not differ when discharged with ( n  = 1051) or without ( n  = 1087) AAD (adjusted odds ratio (OR) 1.13, 95% confidence interval (CI) [0.95–1.35]). The reablation rate was higher and reduced treatment satisfaction was reported more often in those discharged with AAD (reablation: OR 1.30, 95% CI [1.05–1.61]; reduced treatment satisfaction: OR 1.76, 95% CI [1.20–2.58]). Similar rates of recurrences, reablations and treatment satisfaction were found in patients with persistent AF ( n  = 1137) discharged with ( n  = 641) or without ( n  = 496) AAD (recurrence: OR 1.22, 95% CI [0.95–1.56]; reablation: OR 1.21, 95% CI [0.91–1.61]; treatment satisfaction: OR 1.24, 95% CI [0.74–2.08]). The incidence of cardiovascular events and mortality did not differ at follow‐up in patients discharged with or without AAD. In conclusion, the rates of recurrences, cardiovascular events and mortality did not differ between patients discharged with or without AAD after AF catheter ablation. However, AAD should be considered carefully in patients with paroxysmal AF, in whom it was associated with a higher reablation rate and reduced treatment satisfaction. Clinical trial registration: The trial has been registered under the number NCT01197638. Abstract : Prescription of antiarrhythmic drug therapy after catheter ablation for atrial fibrillation is a common daily clinical practice, but there is conflicting evidence on its benefits. In our analysis from the German Ablation Registry the rates of recurrences, cardiovascular events and mortality did not differ between patients discharged with or without antiarrhythmic drug therapy after catheter ablation. However, antiarrhythmic drug therapy should be considered carefully in patients with paroxysmal atrial fibrillation, in whom it was associated with a higher reablation rate and reduced treatment satisfaction.